Fetal diagnosis of congenital ocular toxoplasmosis: a case report - Lacunza Paredes, Rommel Omar (2023)
Congenital toxoplasmosis has serious implications for the prognosis of the newborn,as it can affect the brain and the eye with severe sequelae. The characteristic activelesion of congenital ocular toxoplasmosis is chorioretinitis which is diagnosed atbirth by fundus examination. There are no fetal reports of detection of this lesionby ultrasound, but there are reports of severe lesions such as microphthalmia andcataract. We present a case of congenital toxoplasmosis in the fetus of a pregnantwoman with untreated HIV who showed abnormal images in the eye on ultrasoundthat correlated with lesions in the vitreous and retina in the fundus images at birth.